Risk and protective factors for mental health in elite athletes: a scoping review - Kuettel, A.; Larsen, C. H. (International Review of Sport and Exercise Psychology, 2020)
The purpose of this scoping review was to provide an overview of studies concerning the mental health (MH) of elite athletes and to provide a methodological, conceptual, and applied overview of factors affecting elite athletes` MH. A total of nine reviews and 43 empirical studies were evaluated and are reported in three sections: sample characteristics, research design, and factors affecting elite athletes` MH. These factors were grouped into risk and protective factors and divided into a personal and sport-environmental domain. The studies used quantitative (84%), qualitative (11%), and mixed-method (5%) designs and examined a wide range of sports in different countries. Our review shows that researchers have predominantly examined the prevalence of athletes` mental ill-health (e.g. depression) and the related factors compromising MH. Potential protective factors such as the feeling of autonomy, positive relations in sport and private life, and adequate recovery were highlighted in the qualitative studies. The discussion appraises the findings through a critical lens, focuses on the current state of the research area and the MH definition, limitations, suggested practical implications (e.g. to provide MH literacy to both athletes and coaches), and future research directions (e.g. examining environments that foster elite athletes` MH).